The Challenge - Shapiro, Craig; Ashley, Olsen (USA Dualstar Productions, 2003)
Shane is very into nature and Lizzie is not. They are complete opposites, or so they think. Both enter to be in a TV show and the producers of the show think it would be fun to put them both on the same team when they hate each other. Shane lives in Los Angeles with her mom and Lizzie in Washington, D.C. with her dad. They haven't seen each other in 2 years. They are both put on team Mayan and they have to try and get along for the sake of the team, and their college scholarships. They of course break some romance rules with some guys.
Elisabeth Kruger
Languages : English, German Subtitles : English, German
Keywords: Adventure; Comedy; Family